2021
DOI: 10.1108/bfj-05-2021-0605
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of consumers' motivation towards ethnic food: evidence from Indonesia

Abstract: PurposeThe research objective is to explore consumers' (those of ethnic origin and non-ethnic origin) motivation for choosing ethnic food.Design/methodology/approachA total of 120 respondents were approached at Padang restaurants in Jakarta, and personal interviews were conducted using soft laddering techniques linking to means-end chain (MEC) analysis. The associations among attributes, consequences and values were mapped into a graphical hierarchy to depict the cognitive structure of consuming ethnic food.Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Ethnic foods have greater added value and may require greater investment and skilled culinary staff (Farrer, 2020;Wessendorf & Farrer, 2021). The ethnic heritage food may face some risk factors such as 'adaptation to customer preference', 'costs of ingredients', and 'non-native origin of chef' (Almansouri et al, 2022;Arsil et al, 2022;Mawroh & Dixit, 2023). Most of the ethnic restaurants were composed of Japanese restaurants representing 5.5% of all restaurants.…”
Section: [Figure 2]mentioning
confidence: 99%
“…Ethnic foods have greater added value and may require greater investment and skilled culinary staff (Farrer, 2020;Wessendorf & Farrer, 2021). The ethnic heritage food may face some risk factors such as 'adaptation to customer preference', 'costs of ingredients', and 'non-native origin of chef' (Almansouri et al, 2022;Arsil et al, 2022;Mawroh & Dixit, 2023). Most of the ethnic restaurants were composed of Japanese restaurants representing 5.5% of all restaurants.…”
Section: [Figure 2]mentioning
confidence: 99%
“…The results of a study conducted by Fatima (2022) indicated that buyers tend to prefer products that are affordable or not too expensive. Findings from a study conducted by Arsil (2021) on consumer motivation towards ethnic food concluded that price or financial stability is one of the personal goals that encourage a person to consume ethnic food. Research conducted by Praesri (2022) also found that price is one of the three main factors that influence a tourist's behavior.…”
Section: The Effect Of Price Perception (Price) On Product Awarenessmentioning
confidence: 99%